Mental health nursing at a glance - Smith, Grahame (West Sussex, United Kingdom : John Wiley & Son, Inc., 2015)
Everything you need to know about Mental Health Nursing$1! =(Bat a Glance! From the publishers of the market-leading at a Glance series comes the perfect companion for study and revision for pre-registration mental health nursing students. This brand new nursing title is the perfect accompaniment for pre-registration nursing courses, and is the revision aid that you have been waiting for! Divided into three sections, this book first explores the essential clinical skills needed by nurses, using the NMC Essential Skills Clusters as an organising framework. The second section goes on to look at common disorders and approaches. The third section then discusses the leadership and organisational skills required by nurses, again derived from the NMC standards. Key features: Breaks down complex aspects of mental health care in an accessible and un-intimidating way The perfect revision and consolidation textbook Linked closely with the NMC standards for pre-registration nursing education, and the essential skills clusters framework Explores a broad range of mental health disorders, from care of children right up to care of older people Looks at mental health nursing in all settings, including acute, forensic and community Highly visual colour presentation Includes boxes, summary boxes, reflective opportunities and case studies to improve the learning experience-- Amazons
Part 1 Essential skills -- Part 2 Nursing individuals with mental health needs -- Part 3 Leadership skills.
Includes bibliographical references and index.
Keywords: MENTAL DISORDERS -- NURSING